2017
DOI: 10.1111/liv.13600
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C predicts acute kidney injury and mortality in cirrhotics: A prospective cohort study

Abstract: An episode of AKI itself predisposes to subsequent attacks of AKI in cirrhotics. Scores incorporating CysC can accurately predict the development of AKI and mortality in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
64
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 18 publications
2
64
2
1
Order By: Relevance
“…Studies in patients without cirrhosis have well documented that, even if patients recover from an AKI episode and have normal sCr and GFR, considerable loss of nephrons and renal functional reserve occurs, predisposing these patients not only to future episodes of AKI, but also increased susceptibility to the precipitant minor insults, causing severe damage to the kidneys . Consistent with these findings, we have reported that AKI itself predisposes a patient with cirrhosis to future episodes of AKI . All attempts should therefore be made to prevent repeated episodes of AKI because these are detrimental for the kidneys and may also necessitate a simultaneous liver‐kidney transplant if this remains unabated by leading to CKD.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Studies in patients without cirrhosis have well documented that, even if patients recover from an AKI episode and have normal sCr and GFR, considerable loss of nephrons and renal functional reserve occurs, predisposing these patients not only to future episodes of AKI, but also increased susceptibility to the precipitant minor insults, causing severe damage to the kidneys . Consistent with these findings, we have reported that AKI itself predisposes a patient with cirrhosis to future episodes of AKI . All attempts should therefore be made to prevent repeated episodes of AKI because these are detrimental for the kidneys and may also necessitate a simultaneous liver‐kidney transplant if this remains unabated by leading to CKD.…”
Section: Discussionsupporting
confidence: 83%
“…(5)(6)(7) Consistent with these findings, we have reported that AKI itself predisposes a patient with cirrhosis to future episodes of AKI. (10) All attempts should therefore be made to prevent repeated episodes of AKI because these are detrimental for the kidneys and may also necessitate a simultaneous liver-kidney transplant if this remains unabated by leading to CKD. It can be argued that eGFR is a derived value and may not be appropriate for understanding the functional variations in the kidney after AKI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the following biomarkers have been validated for early detection of AKI: sCysC, serum and urine neutrophil gelatinase-associated lipocalin [23,24], kidney injury molecule 1 [25], urinary insulin-like growth factor-binding protein 7 [26], and urinary interleukin 18 [27]. Among these, sCysC is reportedly an early biomarker for diagnosing AKI in patients receiving cardiac surgery [22,28], with liver cirrhosis [29] or sepsis [24]. However, little is known about an association between sCysC and the risk of AKI after stroke based on KDIGO-AKI criteria in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%